ANALYZING THE INNOVATIVE ENGINEERING TECHNOLOGY STACK - SYEROV, YURIY; TERLETSKA, KHRYSTYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This research paper delves into the analysis of innovative engineering technology stacks, focusing on five pivotal technologies: C#, SQL, Kafka, AWS, and Snowflake. The study highlights the importance of selecting the right technology stack to ensure efficiency, scalability, and innovation in engineering projects. The paper evaluates each technology through a comprehensive comparative analysis based on attributes such as primary use, key advantages, integration capabilities, scalability, security features, cost, and performance. C# is recognized for its robust application development capabilities, offering high performance and strong integration with the .NET ecosystem. SQL stands out for its efficient data manipulation and compatibility with various database management systems, providing robust security features and high performance. Apache Kafka is noted for its real-time data streaming capabilities, scalability, and fault tolerance, making it a cost-effective solution for handling large data streams. AWS is highlighted for its comprehensive cloud computing services, which offer scalability, flexibility, and extensive integration options supported by robust security services. Snowflake is acclaimed for its advanced data warehousing solutions, providing high performance, scalability, and seamless integration with SQL and AWS. Integrating these technologies into a cohesive engineering technology stack enhances engineering projects’ overall performance and scalability. Each technology brings unique strengths, from C#’s application development capabilities to Snowflake’s data warehousing solutions. By leveraging the strengths of each component, engineers can create innovative and efficient solutions tailored to specific project requirements. This paper also addresses engineers’ challenges in selecting and optimizing technology stacks, emphasizing the need for comprehensive frameworks and methodologies. The insights provided aim to guide engineers, developers, and decision-makers in making informed choices that drive technological excellence and innovation. Ultimately, this study aspires to contribute to both the advancement of scientific knowledge and the development of practical applications, serving as a guide for optimizing technology stacks to meet the evolving demands of diverse industries.